Drone, ground robot and human navigation in 3D realistic simulation - Patrascu, Denis Constantin; Montano, Luis; Riazuelo, Luis; Martínez Baselga, Diego (Jornada de Jóvenes Investigadores del I3A, 2025)
This paper presents a new realistic and comprehensive simulation environment for navigation algorithms on a three-dimensional space featuring drones, terrestrial robots and human-like agents. Through several experiments we demonstrate the practical applicability and robust performance of traditional planners in multi-agent 3D scenarios.